Governing death, making persons : the new Chinese way of death - Liu, Huwy-min Lucia, 1978- (Cornell University Press, 2022)
"An ethnography of contemporary urban Chinese death rituals and the Shanghai funeral industry, this book describes how the Chinese Communist Party governed death, how such governance was used to construct specific ideas of persons and citizens, and how such governance has changed after the introduction of market economic reforms"--